Lateral Supracerebellar Infratentorial Approach for Superior Oblique Myokymia: A Case Series. Issue 3 (31st March 2022) - Noro, Shusaku; Seo, Yoshinobu; Honjo, Kaori; Okuma, Masahiro; Asayama, Bunsho; Amano, Yuki; Kyono, Masanori; Hashimoto, Masato; Hanai, Kaori; Nakamura, Hirohiko
Abstract : BACKGROUND: Few reports have shown that superior oblique myokymia (SOM) may result from vascular compression of the trochlear nerve and may be curable using microvascular decompression (MVD). OBJECTIVE: To report the clinical characteristics and surgical treatment of 2 cases of SOM and provide a review of the related literature. METHODS: Two patients with SOM were treated using MVD with the lateral supracerebellar infratentorial approach. The patients underwent diagnostic magnetic resonance imaging and three-dimensional fusion imaging preoperatively. A lateral suboccipital craniotomy was performed in the park-bench position. The trochlear nerve and branches of the superior cerebellar artery were confirmed after opening the cerebellomesencephalic fissure over the tentorial surface of the cerebellum. The vessel, which compressed the root exit zone of the trochlear nerve, was transposed far from the nerve and attached to the surface of the midbrain using Teflon felt and fibrin glue. RESULTS: The first case showed compression on both the ventral and rostral sides of the trochlear nerve root exit zone, and the second showed compression only on the ventral side. Large bridging veins on the tentorial surface of the cerebellum complicated the approach in the second case. Postoperatively, both patients had immediate and complete resolution of symptoms without recurrence at the 24-mo and 17-mo follow-ups, respectively. Five previous reports described the complete resolution of SOM after MVD. CONCLUSION: A presentation of an intermittent fluttering ocular sensation should prompt magnetic resonance imaging for ipsilateral trochlear nerve compression. The lateral supracerebellar infratentorial approach allows safe and efficacious MVD for SOM.